Patterns of Bone Failure in Localized Prostate Cancer Previously Irradiated: The Preventive Role of External Radiotherapy on Pelvic Bone Metastases - Grapin, Mathieu; Quivrin, Magali; Bertaut, Aurélie; Martin, Etienne; Cormier, Luc; Ladoire, Sylvain; Cochet, Alexandre; Créhange, Gilles (Frontiers in Oncology, 2019)
Introduction: External beam radiation therapy (EBRT) can cure localized prostate cancer (PCa) by sterilizing cancer cells in the prostate gland and surrounding tissues at risk of microscopic dissemination. We hypothesized that pelvic EBRT for localized PCa might have an unexpected prophylactic impact on the occurrence of pelvic bone metastases. Material and Methods: We reviewed the data of 332 metastatic PCa patients. We examined associations between the number (≤5 vs. >5) and the location of bone metastases (in-field vs. out-of-field), which occurred at first relapse, and a previous history of EBRT for PCa (EBRT vs. No-EBRT). Results: One hundred and ten patients M0 at baseline were eligible. Fifty-six patients (51%) were in the No-EBRT group, and 54 patients (49%) in the EBRT group. The proportion of patients who developed >5 bone metastases in the bony pelvis was higher in the No-EBRT group vs. the EBRT group: 10 patients (18%) vs. 2 patients (4%), respectively (p = 0.02). By multivariate analysis EBRT was associated with a lesser occurrence of patients who had >5 bone metastases in the bony pelvis (OR = 0.17 [95%CI, 0.04–0.87], p = 0.03). Time to occurrence of bone metastases ≥5 years (OR = 0.10 [95%CI, 0.05–0.19], p < 0.01), prior curative prostate treatment (OR = 0.58 [95%CI, 0.36–0.91], p = 0.02), >5 bone metastases in bony pelvis (OR = 2.61 [95%CI, 1.28–5.31], p < 0.01), >5 bone metastases out of bony pelvis (OR = 1.73 [95%CI, 1.09–2.76], p = 0.02) were all predictive of overall survival. Conclusion: Previous pelvic EBRT for PCa is associated with a lower number of pelvic bone metastases, which is associated with better overall survival.